Quantitative and qualitative assessments of intraosseous neurovascular canals in dentate and posteriorly edentulous individuals in lateral maxillary sinus wall - Mohd Yusmiaidil Putera Mohd Yusof; Michelle Clare Mah; Nor Hidayah Reduwan; Kornkamol Kretapirom; Nur Hafizah Kamar Affendi (Elsevier, 2020)
Objective: Knowledge and evaluation of the blood supply within the maxillary sinus before sinus augmentation are vital to avoid surgical complications. The lateral maxilla is supplied by branches of the posterior superior alveolar artery and infraorbital artery forming intraosseous anastomoses (IA) within the bony lateral antral wall. This study was undertaken to (i) measure mean diameter of IA and its distance from the alveolar ridge within dentate and posteriorly edentulous subjects and, (ii) qualitatively display the relationship of IA throughout its course within the lateral maxillary sinus in cone beam computed tomography (CBCT). Method: Maxillary CBCT images of two-hundred-and-fifty-seven consecutive patients (163 men, 94 women, mean age 42 years) were analyzed. Samples were later divided into dentate (n = 142) and posteriorly edentulous (n = 115) jaws. Using both alveolar ridge and tooth location as reference points, the distance and diameter of IA were assessed. Result: The IA was seen in 63.7% of all sinuses with 68.2% in dentate and 62.4% in edentulous. Mean distance and diameter of IA across the posterior tooth locations were 17.9 ± 3.0 mm and 1.4 ± 0.5 mm (dentate) and 15.1 ± 3.0 mm and 1.0 ± 0.5 mm (posteriorly edentulous), respectively. In each sample, there were no significant differences in distance-alveolar ridge and no significant correlations in diameter-tooth location. A statistically significant Pearson coefficient correlation between diameter and distance in dentate state was observed (r = −0.6). Conclusion: This study reveals that dentate maxillary jaws present larger diameters as compared to posteriorly edentulous jaws, although the IA course remains the same. As these canal structures contain neurovascular bundles with diameters that may be large enough to cause clinically substantial complications, a thorough pre-surgical planning is therefore highly advisable.